THE ANALYSIS OF SLANG WORD FOUND IN OME TV - Nur Aulia Firman; Rizka Indahyanti; Jusmaniar N (English Education Department, Faculty of Teacher Training and Education, Universitas Islam Makassar, 2024)
The reason why analyze the topic of slang is important, because from it we can know the way how communicate either formal and informal, it also identify, peoples, culture, habbit, profes, and life of people in community, by learning slang language we know when we can use formal language and informal language. The researcher attempts to find the processes of word formation and finally used it in human’s life conversation. Besides, choice of slang provides clues to someone’s personal. By understanding the function of slang, people can selected and used the slang words based on the situation and condition when they conduct conversation with others. The design of this research is descriptive qualitative research. The research object in this research was an online chat platform known as OME TV, then researchers analyzed the slang words spoken by other OME TV user with conversation carried out naturally like a normal conversation, and then will reflect on the words of the OME TV user using slang words. After analyzing the findings, the researcher would like to conclude them. In this subchapter, the researcher investigates the slang terms used in OME TV users.As the researcher has proposed the characteristic of slang in the theoretical framework and research findings, the researcher finds there are five types of slang employed by the OME TV users. They are fresh and creative, flippant, imitative, acronym, and clipping. The percentage of fresh and creative is 36.00%, flippant type: 15.00%, imitative type: 21.00%, acronym type: 10,52%, and clipping type: 15.00%. The occurrence of fresh and creative type dominated the slang type used by OME TV users, meanwhile, acronym type is the fewest slang characteristic. This slang characteristic is harder to create compared to the other characteristic.